Application Of Busy Book Play Therapy In Nursing Care For Preschool Children Who Experience Anxiety During Hospitalization At Menggala Regional Public Hospital - Julyanti, Meri; Kusuma, Anggi; Palupi, Rini (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Hospitalization is an emergency or planned process that requires children to stay in the hospital to undergo treatment and care procedures until the child's condition improves and can be returned home. One of the consequences that can occur in children who undergo hospitalization is anxiety. Interventions that can be done to reduce children's anxiety levels while undergoing hospitalization are by doing busy book play therapy. The purpose of this study was to determine the effect of the application of busy book play therapy on the anxiety level of children undergoing hospitalization. Method: This research method uses a descriptive approach with a case study design. Respondents in this case study were two preschool-age children who were indicated to experience anxiety. The intervention provided is busy book play therapy which is carried out once a day for 15 minutes. The level of children's anxiety was measured before and after the implementation of play therapy. Result: The results of the analysis show that there is a decrease in the level of children's anxiety after busy book play therapy. Conclusions: Busy books as one of the creative media that can be used to reduce children's anxiety levels during hospitalization.